GEODYNAMICS OF THE TAIMYR PENINSULA FROM GEOPHYSICAL DATA - D. G. Kushnir (Геодинамика и тектонофизика, 2018)
Recently, a unique geophysical polygon has been created on the Taimyr Peninsula and the adjacent territories. Its densely spaced set of seismic and electric prospecting profiles makes it possible to investigate the structure of the continental lithosphere to the depths of 50–60 km (Fig. 1). The sedimentary cover and the deep horizons of the crust and upper mantle are studied in detail to discover new facts in the history of the geological development of the northern Siberian platform. The contrasting anomalies recorded at the lower crust levels give evidence of considerable changes in density and electrical conductivity, which coincide in plan with the most significant geological structures in the northern regions of Central and West Siberia (Fig. 2). The relationships of the largest uplifts and troughs with the decomposition and compacting processes at the level of Moho are indicative of, on the one hand, the metamorphism occurring under the influence of asthenospheric fluids, and, on the other, the determining role of lithostatic pressure equalization in the formation of these structures. Thus, for the first time, the direct geophysical surveys have shown that the nature of tectonic processes is not limited to only simple horizontal movements of the cratons and associated deformation. Our data shows that the deep geological structure of the study area can be explained, in addition to collision, by the vertical stresses associated with the compaction/decompaction of the crust under the influence of the materials uplifted from the mantle and the lithostatic pressure equalization compensating for the density changes. The vertical tectonic movements are not unidirectional and periodically change their sign, as evidenced by the inversion nature of the largest structures of the sedimentary cover in the Taimyr Peninsula (Fig. 3). In the course of the geological development, the troughs are generally replaced by banks, and uplifts and ridges are involved in subduction, to varying degrees. According to the data obtained, such changes are determined by the differences in the depth levels of the large blocks of the lower crust and upper mantle. These variations seem to play a significant role on other continents; in that regard, their further studies will contribute to a better understanding of global geodynamics.